Chapter: 'Social Facilitation Due to Online Inter-classrooms Tournaments' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Carlos Aguirre (Lecture Notes in Computer Science, 2016)
In this paper we explore the impact of an inter-classrooms math tournament implemented through internet. The strategy is to increase learning through intra-classroom collaboration generated by inter-classroom competition. Ten fourth grade classes with all their students from eight schools participated. During previous weeks students practiced on-line and played a cloud based board game designed to learn word problems. Afterwards, all students participated on an inter-classroom tournament. They played on-line synchronously during 60 min. The game was played in dyads formed from different schools. The list of each classroom average score was published every 5 min on each student computer. We found an important social facilitation effect: a significant improvement on the performance of male students weak on math, and therefore a reduction on the performance gap between mathematically weak and strong male students. The improvement of female students weak on math was also significant but lower.